On the Coexistence of National Companies and Multinational Enterprises - Jörn Kleinert (Kiel Institute for World Economics (IfW), 2003)
National and multinational companies coexist in many sectors of all developed countries. However, economic models fail to reproduce this fact because of the assumption of symmetry between companies. To show that the symmetry assumption is the reason for this failure, a two-country general equilibrium model is set up where multinational enterprises emerge endogenously in reaction to exogenously induced market integration. In a model version with symmetric companies, stable mixed equilibria with national and multinational companies do not exist, because all companies decide to internationalize production at the same conditions. In contrast, if companies are allowed to differ, there exist a wide range of economic conditions where national and multinational companies coexist.
Keywords: L22; F23; F12; 330; Globalization; Multinational Enterprises; Exports; Market Structure; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Allgemeines Gleichgewicht; Mehr-Sektoren-Modell; Zwei-Länder-Modell; Marktstruktur; Globalisierung; Theorie